DISPUTE RESOLUTION OF TRADEMARKS AS JOINT PROPERTY IN DIVORCE CASES: A CASE STUDY OF THE MARTABAK ZEKUT BRAND IN MALANG REGENCY - Marshanda Septya; Lukman Hakim (Widya Gama Intellectual Property Rights, 2026)
The development of the creative economy has made trademark rights an intangible asset with economic value and the potential to become a joint property in marriage. However, the legislation in Indonesia has not explicitly regulated the position or the mechanism for dividing trademark rights as joint property in divorce cases, resulting in legal uncertainty. This study seeks to evaluate the legal status of trademark rights obtained during marriage as joint property, investigate the mechanisms for adjudicating trademark disputes in divorce proceedings, and pinpoint both normative and practical impediments to their resolution. The research uses an empirical juridical method with a case study approach on case number 4217/Pdt.G/2025/PA.Kab.Mlg. Data were obtained through semi-structured interviews with advocates and intellectual property (IP) consultants. The research results indicate that trademark rights obtained and developed during the marriage period can be classified as joint property even though they are formally registered in one party's name, because they have economic value and were obtained during the marriage. Dispute resolution is carried out through the mechanism of dividing joint property in the Religious Court, taking into account the time of acquisition of the trademark, the contributions of the parties, and the economic value of the trademark. The obstacles encountered include the absence of explicit regulations regarding intellectual property as joint property, limited funds for the appraisal of the economic value of the brand, and limited access to evidence. Therefore, regulatory updates are needed that explicitly govern trademark rights as joint property along with standards for assessing its economic value to achieve legal certainty and fair distribution.